A Boost-Buck Three-Port Converter for Solar PV Integrated Electric Vehicle Applications - Kumar A.; Saini D.; Singh R.K.; Prakash S.; Dwivedi D.; Ghosh S.; Chinmaya K.A. (My University, 2025)
This paper presents a novel boost-buck three-port converter (TPC) topology for solar photovoltaic (PV) applications. The three ports are connected to solar PV, battery, and load. The proposed topology aims to supply constant voltage with a continuous current to the load. It functions in different modes such as single input single output (SISO), single input dual output (SIDO), and dual input single output (DISO) based on the available irradiation, battery state of charge (SoC), and load power requirement. The converter is operated with a maximum power point tracking (MPPT) algorithm to extract the maximum attainable power from the solar PV source. The MPPT is achieved without using an additional boost converter, thus optimizing the components in the TPC. With MPPT, TPC can fulfill load demand and reduce battery utilization, increasing battery life. The boost-buck TPC with solar PV is simulated in this paper through Matlab\Simulink. © 2023 IEEE.